Counselling intervention for parents of special needs children (2010)
Over the years, increased awareness of difficulties facing parents of special needs children has been the concern of professionals. Parents are usually disturbed and psychologically maladjusted with the arrival of such children in the family. The arrival in the family obviously affects financial, social, educational and emotional state of such families. As a result of the devastating effect of having special needs children in the family, counselling intervention for parents of such children become inevitable. This paper examines the reaction of parents to the arrival of a child with disability in the family, practical counselling for parents with special needs children which include: counselling parents with gifted and talented children, counselling parents of children with visual impairment, counselling parents of children with learning disabilities, counselling parents of children with hearing impairment, counselling parents with mentally retarded children as well as counselling parents of children with} speech and language disorder. It is recommended that parents should seek early medical attention as soon as they suspect any problem or disability in any of their children. It is also recommended that once the medical doctor confirms the disability, professional Guidance Counsellor must be consulted to counsel the parents on the next line of action.